2022
DOI: 10.3389/fcimb.2022.892864
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Influenza Effect and Mechanisms of Lentinan in an ICR Mouse Model

Abstract: Influenza virus is a serious threat to global human health and public health security. There is an urgent need to develop new anti-influenza drugs. Lentinan (LNT) has attracted increasing attention in recent years. As potential protective agent, LNT has been shown to have anti-tumor, anti-inflammatory, and antiviral properties. However, there has been no further research into the anti-influenza action of lentinan in vivo, and the mechanism is still not fully understood. In this study, the anti-influenza effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 62 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…LNT can reduce oxidative stress-induced apoptosis, and also reduce the expression of pro-inflammatory factors such as TNF-α, IL-8, IL-2, IL-6, IL-22, thereby reducing NF-kB activation, which proves its great potential in the treatment of COVID-19 [31]. Similarly, another study found that LNT can inhibit the overexpression of cytokine storms of TNF-α, IL-1β, IL-4, IL-5, and IL-6 in influenza A viral by modulating the TLR4/MyD88 signaling pathway [32] More interestingly, a randomized controlled human experiment showed that LNT combined with budesonide reduced endogenous anti-inflammatory factor adiponectin IL-17, D-dimer acute severe chronic obstructive pulmonary in patients [33]. Moreover, an animal experiment found that LNT could inhibit oxidative stress in bovine mammary epithelial cells and also reduce the expression of inflammatory factor protein by inhibiting NF-kB and mitogen-activated protein kinase (MAPK), suggesting its great potential in the treatment of mastitis [34].…”
Section: Studies Of Lnt In Inflammation Of Other Systemsmentioning
confidence: 81%
“…LNT can reduce oxidative stress-induced apoptosis, and also reduce the expression of pro-inflammatory factors such as TNF-α, IL-8, IL-2, IL-6, IL-22, thereby reducing NF-kB activation, which proves its great potential in the treatment of COVID-19 [31]. Similarly, another study found that LNT can inhibit the overexpression of cytokine storms of TNF-α, IL-1β, IL-4, IL-5, and IL-6 in influenza A viral by modulating the TLR4/MyD88 signaling pathway [32] More interestingly, a randomized controlled human experiment showed that LNT combined with budesonide reduced endogenous anti-inflammatory factor adiponectin IL-17, D-dimer acute severe chronic obstructive pulmonary in patients [33]. Moreover, an animal experiment found that LNT could inhibit oxidative stress in bovine mammary epithelial cells and also reduce the expression of inflammatory factor protein by inhibiting NF-kB and mitogen-activated protein kinase (MAPK), suggesting its great potential in the treatment of mastitis [34].…”
Section: Studies Of Lnt In Inflammation Of Other Systemsmentioning
confidence: 81%
“…A recent animal experiment with β-glucan extract from Lentinus edodes (Lentinan) confirmed the cytoprotective effect on pulmonary cells and anti-inflammatory activity expressed by the changes in the cytokine spectrum. Furthermore, lentinan showed a high degree of protection against infection with the influenza A virus in mice ( 27 ). It alleviated the pathological changes of infected mice and inhibited inflammatory cytokine levels in the serum and lungs via regulation of the TLR4/MyD88 signalling pathway.…”
Section: Discussionmentioning
confidence: 99%